Removal of methylene blue from aqueous solution by biochar derived from rice husk - Bui Thuong, Huyen; Le Phuong, Thu; Nguyen Thu, Phuong; Le Ngoc, Duy; Vo Dieu, Linh; Pham Le, Anh; Nguyen Lam, Luong; Nguyen Thi, Hue; Le Vinh, Tuan; Mai, Huong; Dinh Thi Mai, Thanh; Herrmann, Marine; et al. (Vietnam Journal of Earth Sciences, 2022)
In this research, rice husk-derived biochar (BC) was evaluated to determine the suitable conditions for the methylene blue (MB) solution adsorption. The characterization of BC was identified by the methods of FT-IR, Raman, and point of zero charges (PZC). The adsorption studies were carried out with BC at different activation conditions (raw BC, HNO3 25% for 4 hours, NaOH 25% for 4 hours, H2O at 90°C for 2 hours and 4 hours, HNO3 25% at 90°C for 2 hours and 4 hours). The activated material then went through an adsorption assessment. Activated BC with NaOH 25% showed its preeminence compared to the other six conditions when reaching the maximum efficiency after the first hour of adsorption. The investigation revealed that the adsorption capacity of the material depends on the activation methods, including pH, activation agent, temperature, and time. The adsorption of BC was consistent with the pseudo-first-order kinetic model and the Langmuir isotherm model, with high correlation coefficients (R2: 0.9838 and 0.9975, respectively). Therefore, it can be concluded that the use of rice husk is feasible for the removal of MB from aqueous solutions.